Consensus guidelines for the management of adult high-grade gliomas for lowand middle-income countries - Syed Ather Enam,; Hafiza Fatima Aziz,; Saqib Kamran Bakhshi,; Ahmed Altaf,; Kaynat Siddiqui,; Asim Hafiz,; Adeeba Zaki,; Muhammad Osama,; Ahmed Gilani,; Pakistan Brain Tumour Consortium: Authors list at the end of the supplement, (Journal of the Pakistan Medical Association, 2024)
High-grade glioma (HGG), a formidable and often incurable disease, presents an even greater challenge in low- and middle-income countries (LMICs) where resources and medical expertise are scarce. This scarcity not only exacerbates the suffering of patients but also contributes to poorer clinical outcomes. Particularly in LMICs, the underrepresentation of the population in clinical trials and the additional hurdles posed by financial constraints underscore an urgent need for contextspecific management strategies. In response, we have rigorously evaluated recent guidelines from leading medical societies, adapting them to suit the specific needs and limitations of the local context in Pakistan. This effort, undertaken in collaboration with local physicians, aims to provide a comprehensive, standardised approach to diagnose, treat, and follow-up with HGG patients. By focussing on the best available clinical evidence and judicious use of limited resources, we strive to improve patient care and outcomes in these challenging settings. Keywords: Patient care, societies, medical, physicians, glioma, brain tumour,